2012
DOI: 10.1016/j.vaccine.2012.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of Y. pestis F1-antigen to gold nanoparticles improves immunogenicity

Abstract: The efficacy of 15 nm gold nanoparticles (AuNP) coated with Yersinia pestis F1-antigen, as an immunogen in mice, has been assessed. The nanoparticles were decorated with F1-antigen using N-hydroxysuccinimide and 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide coupling chemistry. Mice given AuNP-F1 in alhydrogel generated the greatest IgG antibody response to F1-antigen when compared with mice given AuNP-F1 in PBS or given unconjugated F1-antigen in PBS or alhydrogel. Compared with unconjugated F1-antigen, the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 50 publications
0
33
0
1
Order By: Relevance
“…Compared with mice vaccinated with AuNP-F1 in PBS or unconjugated F1-antigen in PBS or alhydrogel, mice vaccinated with AuNP-F1 in alhydrogel generated the highest IgG antibody response to F1-antigen [224]. …”
Section: Other Vaccines For Plaguementioning
confidence: 99%
“…Compared with mice vaccinated with AuNP-F1 in PBS or unconjugated F1-antigen in PBS or alhydrogel, mice vaccinated with AuNP-F1 in alhydrogel generated the highest IgG antibody response to F1-antigen [224]. …”
Section: Other Vaccines For Plaguementioning
confidence: 99%
“…38 A recent study on F1-loaded PLGA/PEG microspheres showed that a single vaccine dose was sufficient to protect mice from challenge. 39 Nanoparticle delivery systems composed of poly(anhydride), 41, 42 gold, 43 lipoproteins, 44 or a hybrid of lipids and biopolymers 23 have been developed for plague vaccines. A single intranasal dose of recombinant F1-V-loaded poly(anhydride) nanoparticles led to prolonged lung disposition 41 and generated high levels of antigen-specific antibody responses, 42 with the overall kinetics dictated by the chemical composition, hydrophobicity, and degradation rate of poly(anhydride) particles.…”
Section: Particulate Vaccines Against Category a Bioterrorism Agentsmentioning
confidence: 99%
“…They found that the conjugate produced higher titers of anti‐NgR antibody than that with Freund's adjuvant, and improved the repair of spinal cord‐injured rats . Yersinia pestis F1‐antigen coated on the surface of 15 nm AuNPs generated a greater IgG antibody response in mice compared to F1‐antigen alone …”
Section: Gold Nanomaterialsmentioning
confidence: 99%